Pemaknaan Maskulinitas pada Majalah Cosmopolitan Indonesia - Sumekar Tanjung (Program Studi Ilmu Komunikasi, 2012)
Nowadays, the position of men and women has no difference. Men and women are treated equally as a commodity. The phenomenon of hegemonic masculinity have been well understood, despite the fact that media especially magazine, is a medium for the contest between masculinity and femininity. This study focuses on how masculinity of man is represented in Cosmopolitan Indonesia Magazine (August, September, October and December 2011 editions).